Alkoholizm wśród osób starszych – czynniki ryzyka, konsekwencje i możliwości wsparcia - Toroń-Fórmanek, Barbara; Borek, Paulina (Studia Edukacyjne, 2025)
Due to demographic changes, it is essential to take action on multiple levels to promote the health of seniors, including addressing alcohol consumption. Limited adaptive capacities to consequences may, as a result, lead to side effects that increase the risk of adverse outcomes and stress. Addictions among seniors are often overlooked, and their occurrence may be attributed to other coexisting conditions. Actions related to addiction are primarily targeted at younger age groups, which leads to the marginalization of risks within the senior population. The scale of alcohol-related problems in this social group is particularly significant due to the risk of their manifestation, which may affect both their physical and mental functioning. The aim of the article is to analyze the risk factors contributing to the development of alcohol addiction in the elderly population, to present the potential health and social consequences of alcohol abuse in old age, and to indicate possible directions of therapeutic and preventive support. The subject of the study is the phenomenon of alcoholism among seniors in the context of demographic, psychological, and social determinants.